Home Science Extension as a Pathway to Rural Women’s Empowerment: A review - Akanksha Singh; Prachi Shukla; Akhilesh Kumar Yadav; Suman Devi (The Bioscan, 2026)
Rural women play a pivotal role in India’s agricultural and household systems, contributing substantially to farm labour, food processing, nutrition management, and family care. Despite this contribution, they continue to face structural constraints related to access to education, extension services, productive resources, markets, and decision-making power, resulting in persistent economic, nutritional, and social vulnerabilities. Home science, as an applied and interdisciplinary discipline, offers a holistic framework to address these challenges by integrating nutrition, health, food processing, family resource management, and livelihood development. In India, Krishi Vigyan Kendras (KVKs) serve as the primary grassroots extension institutions delivering home science interventions tailored to rural women.